(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The tribal communities like Bhil, Pawra, Tadvi and Korku are gold mines of traditional veterinary knowledge as they have been using plants to keep their livestock healthy and free from diseases. Several factors of modern civilization day by day is getting diminished this knowledge.